1999
DOI: 10.1088/0953-8984/11/50/328
|View full text |Cite
|
Sign up to set email alerts
|

An equation of state applied to solid up to 1 TPa

Abstract: In this paper, an isothermal three-parameter equation of state (EOS) of solid is presented in the form V /V 0 = f (P ). The proposed EOS uses three parameters expressible in terms of B 0 , B 0 and B 0 , denoting bulk modulus and its first and second pressure derivatives at zero pressure. The new EOS is applied to the isotherms of ionic, metallic, quantum and rare-gas solid, with pressures ranging from zero to variable maximum pressures of up to 1 TPa (= 10 Mbar). The fits are uniformly excellent, and equally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…The experimental data of V 0 and fitted parameters B 0 (GPa) and B 0 for BN, ASJ, MRS3, SMS3, and SMS4 EOSs. The values of fitted parameters for KD EOS refer to [40], for other EOSs refer to [18]. In our calculations, it is found that the parameters of Baonza EOS are sensitive to the fitting approach.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The experimental data of V 0 and fitted parameters B 0 (GPa) and B 0 for BN, ASJ, MRS3, SMS3, and SMS4 EOSs. The values of fitted parameters for KD EOS refer to [40], for other EOSs refer to [18]. In our calculations, it is found that the parameters of Baonza EOS are sensitive to the fitting approach.…”
Section: Resultsmentioning
confidence: 93%
“…Only the KD EOS is a three-parameter equation, the other EOSs are two-parameter equations. All experimental data for V (P, T 0 )/V (0, T 0 ) are taken from Kennedy and Keeler (1972) [35], except for n-H 2 [36 -38], W [39], and NaCl [40]. The average fitting errors for pressure (P = f (V )) have been listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] Roy and Roy 39 gave a good review and evaluate the fittings of the currently used EOSs. Their proposed 40 threeparameter empirical EOS is…”
Section: Empirical Eossmentioning
confidence: 99%
“…They have attracted attention of many researchers [1][2][3][4][5][6][7][8][9]. The study of effect of temperature and pressure on hydrides is also very important from structural point of view [2][3][4][5][6][7][8][9][10][11][12]. These hydrides undergo structural phase transition B 1 −B 2 at elevated pressure [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These hydrides undergo structural phase transition B 1 −B 2 at elevated pressure [2][3][4][5][6]. The effect of temperature has also been investigated by many workers [10][11][12]. B 1 −B 2 transition can be explained by the Berger mechanism [13] by two ion rhombohedral primitive cells.…”
Section: Introductionmentioning
confidence: 99%